Alchemilla straminea in redetermined herbarium specimens – new to Finland and northern Europe - Piirainen, Mikko (Memoranda Societatis pro Fauna et Flora Fennica, 2017)
Alchemilla straminea was determined in herbarium material that had been collected from at least four adjacent localities at Kangasjärvi in the municipality of Hyrynsalmi, Kainuu, in eastern central Finland in 1952–1978. The species is new to Finland and northern Europe. Kangasjärvi served as a German military depot during World War II in 1941–1944. Large numbers of horses and mules were housed in the area, and hay for the animals was imported from Central Europe. After the war, Kangasjärvi was known for its rich flora of German polemochores, some of which are still extant in the area. The origin of A. straminea is probably from hay cut from natural alpine meadows in the area of the Alps, Jura and the Schwarzwald. Several polemochorous Alchemilla species from World War II still have established populations in Finland. A. straminea survived at least c. 35 years. Its present status is unknown, as the locality has not been studied thoroughly enough.